Accounting narratives and disclosures in reporting the case of Letters from the Management Board Presidents of selected companies in the light of narrative economics - Bąk, Melania (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: At the initial stage of accounting evolution it was considered an economic science, closely related to the activities performed by economic entities in economic conditions. Therefore, narratives in economics should be considered a determinant for the development of narratives in accounting. The indication of narrative economics as a reference point for narration in accounting supplements the research gap, since nowadays narratives in accounting are most often interpreted as the narratives prepared by companies and addressed to the potential stakeholders in the context of achieving specific goals by the management board and company executives. Aim: The purpose of the article is to address the phenomenon of narrative accounting in the light of narrative economics and the evolution of reporting targeting non-financial information. Results: Economic narratives facilitate the understanding of numbers, extend and supplement financial information and allow for the interpretation of economic processes. The narratives coming from economics are processed and disclosed in accounting. They are an indispensable attribute of modern accounting as well as its narration. Reporting is an important instrument allowing narration in accounting (primarily non-financial reporting). The research confirms: positive messages included in the analysed Letters from Management Board Presidents; references in the text to economic factors and the characteristic financial and social activities in specific companies; indication of the key words in the text, among which the dominant ones are those with a positive overtone and also the ones relating to non-material resources; creating narrative reporting in order to develop and strengthen relationships with potential stakeholders.